New Ferulic Acid and Amino Acid Derivatives with Increased Cosmeceutical and Pharmaceutical Potential - Ewa Janus; Luan Ramalho Pinheiro; Anna Nowak; Edyta Kucharska; Ewelina Świątek; Natalia Podolak; Magdalena Perużyńska; Katarzyna Piotrowska; Wiktoria Duchnik; Łukasz Kucharski; Adam Klimowicz (MDPI AG, 2022)
Ferulic acid (FA) has been widely used in the pharmaceutical and cosmetics industry due to its, inter alia, antioxidant, antiaging and anti-inflammatory effects This compound added to cosmetic preparations can protect skin because of its photoprotective activity. However, the usefulness of FA as a therapeutic agent is limited due to its low solubility and bioavailability. The paper presents the synthesis, identification, and physicochemical properties of new FA derivatives with propyl esters of three amino acids, glycine (GPr[FA]), L-leucine (LPr[FA]), and L-proline (PPr[FA]). The NMR and FTIR spectroscopy, DSC, and TG analysis were used as analytical methods. Moreover, water solubility of the new conjugates was compared with the parent acid. Both ferulic acid and its conjugates were introduced into hydrogel and emulsion, and the resulting formulations were evaluated for stability. Additionally, in vitro penetration of all studied compounds from both formulations and for comparative purposes using Franz diffusion cells was evaluated from the solution in 70% (v/v) ethanol. Finally, cytotoxicity against murine fibroblasts L929 was tested. All of the analyzed compounds permeated pig skin and accumulated in it. LPr[FA] and PPr[FA] were characterized by much better permeability compared to the parent ferulic acid. Additionally, it was shown that all the analyzed derivatives are characterized by high antioxidant activity and lack of cytotoxicity. Therefore, they can be considered as an interesting alternative to be applied in dermatologic and cosmetic preparations.